Effectiveness of the Use of Information Technology in the Merdeka Mengajar Platform in Islamic Religious Education Learning in Pringsewu Regency - Humammi, Hanifah; Syafei, Imam; Lutfi, Muhammad Khoirul; Janah, Siti Roudhotul (CV. Bimbingan Belajar Assyfa, 2024)
This research aims to evaluate the effectiveness of using information technology through the Merdeka Mengajar Platform in Islamic Religious Education learning at SMP Negeri 1 Gading Rejo, Pringsewu. This research uses a field research method with a qualitative descriptive approach. Data was collected through interviews, observation, and documentation, and analyzed using thematic analysis techniques. The research results show that using the Merdeka Mengajar Platform has increased student engagement and facilitated more flexible access to learning materials. In addition, this platform supports teachers in presenting material more interactively and interestingly. These findings indicate that integrating information technology into learning can improve the quality of Islamic religious education in schools.ujuan penelitian ini adalah: (1) Untuk menganalisis efektivitas penggunaan teknologi informasi dalam platform merdeka mengajar. (2) Untuk menganalisis Platform Merdeka Mengajar dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 1 Gading Rejo Pringsewu. Jenis penelitian ini adalah penelitian lapangan atau field research, yang bersifat deskriptif kualitatif. Penelitian ini diharapkan dapat mengungkap gambaran mengenai realitas sasaran penelitian, yakni tentang penggunaan Platform Merdeka Mengajar di SMP Negeri 1 Gading Rejo Pringsewu. Penggunaan platform Merdeka Mengajar dalam pembelajaran Pendidikan Agama Islam. Dengan menggunakan Platform Merdeka Mengajar, pembelajaran Pendidikan Agama Islam di SMP 1 Gading Rejo telah mengalami peningkatan signifikan. Platform ini memberikan fleksibilitas bagi siswa untuk mengakses materi pembelajaran secara daring sesuai dengan jadwal dan kebutuhan mereka.